Characteristics of clients with nicotine dependence and short-term abstinence: findings from the USM Tobacco Quitline Service in Malaysia - Mohd Fadhli Razali; Sulastri Samsudin; Maizurah Omar; Balamurugan Tangiisuran; Asdariah Misnan; Noor Afiza Abd. Rani; Nur Fariha Abd. Ghani; Norasikin Badaruddin (Tobacco Induced Diseases, 2018)
Background Globally, quitlines have been shown to be an effective means for smoking cessation. The success of quitting among smokers is contributed by many factors such as nicotine dependence, motivation, income and educational levels, previous quit attempts, environmental characteristics and quit methods. This study will determine the characteristics of clients with nicotine dependence and short- term abstinence (one month duration) among those registered with the USM Tobacco Quitline Service.